Radiological Evaluation of Dacryocystitis in Children Using CT-Scan - Khairunnisa Sekar Ayu; Yenny R. Mulyanto; Ryan Indra (Lembaga Pengembangan Kinerja Dosen, 2026)
Dacryocystitis is an inflammation of the lacrimal sac resulting from nasolacrimal duct obstruction, which interferes with tear drainage and leads to secondary infection. It commonly occurs in children and individuals over 40 years old, characterized by pain, redness, and swelling in the medial canthus area. This study aims to evaluate radiological findings of dacryocystitis in a child using Computed Tomography (CT) Scan as the main diagnostic modality. The descriptive case study involved a six-year-old girl with right eye pain and swelling for seven days before hospitalization. Physical examination revealed swelling, hyperemia, and tenderness in the right lower eyelid. Orbital CT-scan showed a hypodense lesion in the right inferior orbital region extending to the inferior canaliculus and proximal lacrimal sac, with periorbital swelling confirming dacryocystitis. Follow-up imaging demonstrated lesion enlargement, indicating progressive inflammation. The patient received antibiotic and supportive therapy, leading to clinical improvement after treatment. CT-scan examination proved essential in confirming diagnosis, assessing inflammation severity, and guiding appropriate treatment planning.